Programme characteristics associated with weight change following behavioural weight loss programmes: a systematic review and meta-analysis - Hartmann-Boyce, J; Theodoulou, A; Oke, J; Butler, A; Hobbs, F; Jebb, S; Aveyard, P (BMJ Publishing Group, 2021)
Objective: To determine if characteristics of behavioural weight loss programmes (BWMPs) influence weight change trajectories following programme end.